Pengabdian Masyarakat Melalui Pembuatan Fitur Navigasi pada Kertas Kerja Pemeriksaan Audit di Suatu KAP di Surakarta - Muhammad Karin Pramesti; Nayya Faqda Iksaniya; Muhammad Chaerul Ichsan; Nurhasan Hamidi (Jurnal Dharma Indonesia, 2023)
A Surakarta-based accounting firm, identified as Firm X, struggles with unorganized data input and lacks navigational features in its workbooks, causing efficiency issues. This research utilized a method involving needs analysis, design development, testing, and evaluation. After auditor interviews, the new workbook design received positive feedback for its visual appeal, color scheme, and organized sheet layout. This redesign streamlines processes, saving time, and enhancing usability, particularly for novices